Dynamics of dye release from nanocarriers of different types in model cell membranes and living cells - Tkacheva, T.N.; Yefimova, S.L.; Klochkov, V.K.; Sorokin, A.V.; Malyukin, Yu.V. (Вiopolymers and Cell, 2014)
Aim. To study the dynamics of lipophilic content release from nanocarriers of different types, organic molecular ensembles and inorganic nanoparticles (NPs) in vitro experiments. Methods. Two-channel ratiometric fluorescence detection method based on Forster Resonance Energy Transfer, fluorescent spectroscopy and micro-spectroscopy have been used. Results. It has been found that the profiles of lipophilic dyes release from organic nanocarriers (PC liposomes and SDS micelles) and inorganic ones (GdYVO₄:Eu³⁺ and CeO₂ NPs) are well fitted by the first-order reaction kinetics in both model cell membranes and living cells (rat hepatocytes). The dye release constants (K) and half-lives (t1/2) were analyzed. Conclusions. GdYVO₄:Eu³⁺ and CeO₂ NPs have been shown to provide faster lipophilic content release in model cell membranes as compared to PC liposomes. Negatively charged or lipophilic compounds added into nanocarriers can decrease the rate of lipophilic dyes release. Specific interaction of GdYVO₄:Eu³⁺ NPs with rat hepatocytes has been observed.